Working memory and background knowledge - Cognitive science in the design classroom - Trogu, Pino (FormAkademisk, 2015)
This article discusses two universal principles from cognitive psychology, and proposes some ways in which those principles relate to graphic design. The two most important principles are first, the strict constraints of working memory, a function which persists for only a few seconds, and second, the finding that perceptions and meanings are mediated by the cultural knowledge of viewers, including their knowledge of design conventions and genre. Better de-signs are likely to emerge from the designer’s familiarity with these psychological and cultur-al principles. Visual examples, including maps and student projects, illustrate how the two principles are useful for classroom instruction.